A chromodomain protein, Chp1, is required for the establishment of heterochromatin in fission yeast - Sadaie, Mahito (Nature Publishing Group, 2004)
The chromodomain is a conserved motif that functions in the epigenetic control of gene expression. Here, we report the functional characterization of a chromodomain protein, Chp1, in the heterochromatin assembly in fission yeast. We show that Chp1 is a structural component of three heterochromatic regions—centromeres, the mating-type region, and telomeres—and that its localization in these regions is dependent on the histone methyltransferase Clr4. Although deletion of the chp1(+) gene causes centromere-specific decreases in Swi6 localization and histone H3-K9 methylation, we show that the role of Chp1 is not exclusive to the centromeres. We found that some methylation persists in native centromeric regions in the absence of Chp1, which is also true for the mating-type region and telomeres, and determined that Swi6 and Chp2 are critical to maintaining this residual methylation. We also show that Chp1 participates in the establishment of repressive chromatin in all three chromosomal regions. These results suggest that different heterochromatic regions share common structural properties, and that centromeric heterochromatin requires Chp1-mediated establishment steps differently than do other heterochromatic regions.